Evaluación técnico-financiera para la implementación de un laboratorio de reología en el Instituto Nacional de Metrología de Colombia (INM) (2019)
The INM aims at the national coordination of scientific and industrial metrology. At the beginning of the research, a rheology study focused on four industries (food, pharmaceutical, petrochemical, paints) was presented as a priority for the INM. As a central research axis, a technical study of the conditions required by the laboratory such as equipment, work area, laboratory conditions, etc. was carried out. As a final point, different financial indicators are analyzed to determine the financial viability for laboratory implementation.